Clonal Spread of 16S rRNA Methyltransferase-Producing Klebsiella pneumoniae ST37 with High Prevalence of ESBLs from Companion Animals in China - Xia, Jing; Fang, Liang-Xing; Cheng, Ke; Xu, Guo-Hao; Wang, Xi-Ran; Liao, Xiao-Ping; Liu, Ya-Hong; Sun, Jian (Frontiers in Microbiology, 2017)
We screened thirty Klebsiella pneumoniae isolates from dogs and cats at a single animal hospital in Guangdong Province, China. Among them, 12 K. pneumoniae strains possessed high-level resistance to amikacin and gentamicin and these were screened for 16S rRNA methyltransferase genes. And then the genes positive isolates were detected for other resistance determinants (ESBLs and AMEs) and analyzed by PFGE, multilocus sequence typing, PCR-based replicon typing and plasmid analysis. The genetic profiles of rmtB were also determined by PCR mapping. The 12 16S-RMTase gene-positive isolates were rmtB (11/30) and armA (2/30) with one isolate carrying both genes. Extended spectrum β lactamase genes were represented by blaCTX-M-55 (9/12), blaCTX-M-27 (2/12) and blaCTX-M-14 (1/12). The 12 16S-RMTase containing strains were grouped into five clonal patterns and ST37 was the most prevalent sequence type. Ten rmtB-bearing plasmids conjugated successfully and all belonged to IncN and IncF (F33:A-:B-) incompatibility groups. Nine of the transconjugants carried a 97 kb plasmid and the other harbored both ~60 kb and ~200 kb plasmids. rmtB and blaCTX-M-55 were present on the same plasmid and indicated the co-transfer of these two genes, with the rmtB gene showing highly relevant relationships with IS26 and Tn3. Our findings suggested a high prevalence of 16S-RMTase genes in K. pneumonia ST37 from dogs and cats. Additional studies are needed to trace the evolutionary path of this type of resistance among the K. pneumonia isolates, and to determine whether they have been transferred to humans.